Accommodating Audience Needs in Islamic Subtitling: A Case of Manipulation? - Elgebaly, Nermine (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The field of subtitling has its own spatial and temporal challenges and constraints, which are further compounded in the case of translating Islamic programmes because of the culture-specific translation problems. Subtitlers have to bridge the cultural gap and accommodate audience needs, without the possibility of resorting to footnotes, glossaries, or explanatory notes. This may warrant some conscious changes to the Arabic source text (ST) to achieve maximum intelligibility in the English target text (TT). Manipulation in translation has mostly been used in a negative sense to mean a vicious attempt to alter STs to promote a dominant culture and ideology. In Islamic subtitling on the satellite channel Iqraa, this is far from being true as the Arabic text rewriting involves the activation of certain strategies to render complex Islamic concepts intelligible to a wider, international audience. This paper examines how audiovisual translators of the Iqraa satellite channel make conscious alterations to the ST, especially in the case of Iltifat – a rhetorical device in Arabic utilizing a reference/referent shift to involve the audience and achieve a heightened dramatic effect – as well as in the case of code-switching between Classical and Colloquial Arabic. The case study under scrutiny is two audiovisual programmes by two Islamic televangelists, who speak in Egyptian Colloquial Arabic.